Longitude patterns in breeding bird species richness in cities - Sakhvon, Vital V. (Journal of the Belarusian State University. Ecology, 2020)
This paper analyses changes in the breeding bird species richness in cities with alteration of geographical longitude. The study has analyzed the total breeding avifauna in 16 cities from Western Europe to European Russia. The study has found that the maximum richness of breeding bird species is observed in cities in Central and Eastern Europe (146–151 species), whereas the minimal – in the westernmost (71 species) and easternmost (90 species) cities. The study analyzed in detail the avifauna in Warsaw, Lviv, Brest, Voronezh, and Orenburg, which are situated in different longitudes, to confirm that the dynamics of the breeding bird species richness in urban areas are determined by the bird species diversity (native avifauna) in regional natural landscapes. The main differences in the structure of urban avifauna are connected with different participation of dendrophilic species in urban bird assemblages. The structure of dendrophilic species in urban bird assemblages is determined by the zonality of wood vegetation.
Keywords: avifauna; structure of avifauna; urban birds; bird species richness; urban; city; synurbization